2000
DOI: 10.1001/archotol.126.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Ipsilateral Neck Cancer Recurrences After Elective Supraomohyoid Neck Dissection

Abstract: The incidence of neck recurrence after selective neck dissection was 4.5%, and it occurred either inside (57.1%) or beyond (42.9%) the limits of the selective neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
9

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
1
21
0
9
Order By: Relevance
“…2,3,7 In cases of clinically negative necks (N0), the clinical examination may present up to a 40% failure rate in detecting lymph node metastases. 2,3,8,9 A combination of clinical and imaging examinations is essential for detecting metastatic lymph nodes and establishing the prognosis. 10,11 Of the imaging modalities, computed tomography (CT) and magnetic resonance imaging (MRI) seem to be the most appropriate for the pre-therapeutic staging of head and neck tumors, because they provide information on the extent of the lesion, infiltration of large vessels and metastases in lymph nodes.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…2,3,7 In cases of clinically negative necks (N0), the clinical examination may present up to a 40% failure rate in detecting lymph node metastases. 2,3,8,9 A combination of clinical and imaging examinations is essential for detecting metastatic lymph nodes and establishing the prognosis. 10,11 Of the imaging modalities, computed tomography (CT) and magnetic resonance imaging (MRI) seem to be the most appropriate for the pre-therapeutic staging of head and neck tumors, because they provide information on the extent of the lesion, infiltration of large vessels and metastases in lymph nodes.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…Some authors have demonstrated that over 20% of neck palpation-negative patients have indeed occult neck metastases. 10,11 Another important factor for accurately estimating survival is a long-term follow-up of patients with oral malignancies. 12 Local recurrent tumours following primary treatment are a relatively common occurrence after treatment, and are, sometimes, also not detected clinically.…”
Section: Introductionmentioning
confidence: 99%
“…This outcome can also be affected by the operator's experience and judgement. Of 4.5% neck recurrences after selective neck dissection, Carvalho et al (2000) found 57.1% of them to be inside the limits of dissection. Similarly, Anderson et al (2002) and Chepeha et al (2002) reported two-thirds of recurrences following SOHND to be in the field of dissection.…”
Section: Discussionmentioning
confidence: 87%